ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TELLER TERBAIK DENGAN MENGGUNAKAN METODE PROFILE MATCHING PADA PT. BANK CENTRAL ASIA, TBK - Aileen, Aileen; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
In an effort to develop tellers, PT. Bank Central Asia chooses the best teller every year as a form toprovide work motivation to tellers. The best teller selection system at PT. Bank Central Asia, Tbk theJambi has been carried out manually by direct observation from the section head and knowledge testwhich requires a long time and is not objective, and has not been well documented so that it requires aninformation system that can help in the selection process of the teller in the selection process anddocumentation process. In this case, the appropriate information system is a decision support systemusing the Profile Matching method. Profile Matching method is very appropriate to use because thismethod measures the ability of the teller according to the target profile that has been. The systemmodeling tool used is UML (Unified Modeling Language). This study produced a prototype decisionsupport system for selecting the best tellers that can be implemented in accordance with existing needs,especially in the selection of the best tellers at PT. Bank Central Asia, Tbk Jambi so that it will shortenthe time needed and the electoral process will take place objectively.